Phenomenology in Poland. - Górniak, Krystyna (Spring; Philosophy., 1999)
Keywords: dept.phi; faculty_collection; sabbatical_report

Jacques Lacan and the Poetic Unconscious. - Pettigrew, David (Fall;Philosophy., 1998)
Keywords: dept.phi; faculty_collection; sabbatical_report

Information Ethics: A Comprehensive Introduction. - Bynum, Terrell Ward (1995)
Keywords: dept.phi; faculty_collection; sabbatical_report

Metaphilosophy. - Metaphilosophy Foundation (B. Blackwell for the Metaphilosophy Foundation, 1970)
Publication Title: Metaphilosophy.
Keywords: Periodicals; Philosophy; dept.phi; faculty_collection

The Digital Phoenix: How Computers Are Changing Philosophy - Bynum, Terrell Ward; Moor, James H.; American Philosophical Association Committee on Philosophy and Computers (Blackwell Publishers, 1998)
Keywords: Data processing; Data processing; Philosophy; Philosophy; Study and teaching; dept.phi; faculty_collection

Heidegger and the Subject - Raffoul, François (Humanities Press, 1998)
Keywords: Contributions in concept of subject; Subject (Philosophy); Heidegger; Martin; 1889-1976; dept.phi; faculty_collection

Heidegger and the Question of Time - Dastur, Françoise (Humanities Press, 1997)
SCSU Faculty Scholar Award
Keywords: 20th century; Contributions in philosophy of time; Time; Heidegger; Martin; 1889-1976; History; award_winner; dept.phi; faculty_collection

Disseminating Lacan - Pettigrew, David; Raffoul, François (State University of New York Press, 1996)
Keywords: Lacan; Jacques; 1901-1981; Lacan; Jacques; 1901-1981; Psychoanalytic Theory; Psychoanalytic Interpretation; dept.phi; faculty_collection

Radical Philosophy of Law: Contemporary Challenges to Mainstream Legal Theory and Practice - Caudill, David Stanley; Gold, Steven Jay (Humanity Books, 1995)
Keywords: Philosophy; Radicalism; Sociological jurisprudence; Law; dept.phi; faculty_collection

Moral Controversies: Race, Class, and Gender in Applied Ethics - Gold, Steven Jay (Wadsworth Pub. Co., 1993)
Keywords: Moral conditions; Social ethics; United States; Social problems; Sociological jurisprudence; Applied ethics; United States; dept.phi; faculty_collection

Nature's Perspectives: Prospects for Ordinal Metaphysics - Marsoobian, Armen; Wallace, Kathleen; Corrington, Robert S. (State University of New York Press, 1991)
Keywords: Buchler; Justus; 1914-1991; Metaphysics; Order (Philosophy); Naturalism; dept.phi; faculty_collection

Applying Philosophy - Bynum, Terrell Ward; Vitek, William (Metaphilosophy Foundation, 1988)
Keywords: Philosophy; dept.phi; faculty_collection

Computers & Ethics. - Bynum, Terrell Ward (1985)
Keywords: Ethics; Computers; Moral and ethical aspects; dept.phi; faculty_collection

Claude Lévi-Strauss: Social Psychotherapy and the Collective Unconscious - Shalvey, Thomas (University of Massachusetts Press, 1979)
SCSU Faculty Scholar Award
Keywords: Lévi-Strauss; Claude; Ľvi-Strauss; Claude; Subconsciousness; Anthropology; Cultural; Philosophy; Psychology; Social; award_winner; dept.phi; faculty_collection

Gandhi's Idea of Non-Violence. - Mohan, Pandiri Krishna (Thesis Ph. D.–Southern Illinois University, Dept. of Philosophy, April., 1972)
Keywords: Gandhi; Mahatma; 1869-1948; India; Politics and government; dept.phi; faculty_collection

The Common Philosophy, - Peterson, Forrest H. (Philosophical Library, 1972)
Keywords: Philosophy; Naturalism; Existentialism; Human beings; dept.phi; faculty_collection

Philosophic Anthology from Plato to Nietzsche. - Rethis, Michael (Kendall/Hunt Pub. Co, 1971)
Keywords: Philosophy; dept.phi; faculty_collection

A Philosophy of Man and Society - Peterson, Forrest H. (Philosophical Library, 1970)
Keywords: Human beings; Sociology; History; Philosophy; Philosophy; Education; dept.phi; faculty_collection

A Philosophical Perspective of Education - Peterson, Forrest H. (Wm. C. Brown, 1964)
Keywords: Education; Philosophy; dept.phi; faculty_collection

Foucault’s critique of functional marxism - Gold, S.J. (Rethinking Marxism, 1990)
2 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Saying, singing, or semiotics: "Prima la musica e poi le Parole" revisited - Marsoobian, A.T. (Journal of Aesthetics and Art Criticism, 1996)
2 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Creationism as science: what every teacher-scientist should know. - Gatzke, Ken W (Science Education, 1985)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-931-368-923-223 tex.type: [object Object]
Keywords: dept.phi

Introduction - van der Hoven, J; Bynum, T; Gotterbarn, D; Rogerson, S (Journal of Business Ethics, 1999)
0 citations (Crossref) [2023-10-31] tex.eissn: 1573-0697 tex.orcid-numbers: Page, Edward/0000-0002-7117-3342 tex.unique-id: ISI:000081927400001
Keywords: dept.phi

Symposium on computer ethics - Bynum, Terrell Ward (Metaphilosophy, 1997)
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/100-483-080-711-229 tex.type: [object Object]
Keywords: dept.phi

Book Review: The catholic church and antisemitism: poland, 1933–1939. by ronald modras. langhorne, penn.: harwood academic publisher, 1994. 429 pp. 48.00 - Gorniak-Kocikowska, Krystyna (Journal of Church and State, 1997)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/133-524-633-010-63X tex.type: [object Object]
Keywords: book.review; dept.phi

The computer revolution and the problem of global ethics - Gorniak-Kocikowska, Krystyna (Science and Engineering Ethics, 1996)
The author agrees with James Moor that computer technology, because it is 'logically malleable', is bringing about a genuine social revolution. Moor compares the computer revolution to the 'industrial revolution' of the late 18th and the 19th centuries; but it is argued here that a better comparison is with the 'printing press revolution' that occurred two centuries before that. Just as the major ethical theories of Bentham and Kant were developed in response to the printing press revolution, so a new ethical theory is likely to emerge from computer ethics in response to the computer revolution. The newly emerging field of information ethics, therefore, is much more important than even its founders and advocates believe.
32 citations (Crossref) [2023-10-31] Citation Key Alias: pop00034 tex.type: [object Object]
Keywords: Computer ethics; Computer revolution; Global ethics; Industrial revolution; Printing revolution; Professional ethics; dept.phi

Introduction and overview: Global information ethics - Bynum, Terrell Ward; Rogerson, Simon (Science and Engineering Ethics, 1996)
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-678-042-833-054 tex.type: [object Object]
Keywords: dept.phi